Virulence Factors of Gastrointestinal Pathogens Escherichia coli, Salmonella enterica, and Proteus mirabilis Targeted by Luteolin: A Microbioinformatics Study - Muhammad Sulthan Rizqy Syamsuddin; Rian Ka Praja; Nawan Nawan; Astrid Teresa; Agnes Frethernety (Biology, Medicine, & Natural Product Chemistry, 2026)
Luteolin is a natural flavonoid with broad-spectrum antibacterial, anti-inflammatory, and metabolic regulatory properties, making it a promising antivirulence candidate against gastrointestinal pathogens such as Escherichia coli ATCC8739, Salmonella enterica CT18, and Proteus mirabilis HI4320. The increasing global burden of antimicrobial resistance highlights the need for alternative strategies targeting virulence rather than bacterial viability. This study aimed to investigate the interaction of luteolin with virulence-associated proteins of these pathogens using a microbioinformatics-based approach. Protein–compound interaction networks were analyzed using STITCH v5.0, and the resulting FASTA sequences were evaluated using VICMPred, VirulentPred, BepiPred v1.0, MHC I and II Binding Predictions, and PSORTb v3.0 to determine functional classes, virulence potential, immunogenic epitopes, and subcellular localization. The analysis identified multiple virulent proteins targeted by luteolin in each pathogen: cirA, ECs4935, yedX, rbbA, pykA, and pykF in E. coli; fepA, iroN, iroB, sitA, and pykF in S. enterica; and ireA and PMI2409 in P. mirabilis. These proteins are associated with outer membrane iron acquisition, epithelial adhesion, energy metabolism, and cellular homeostasis. Epitope prediction revealed numerous high-scoring B-cell and T-cell binding regions across all virulent proteins, indicating strong immunogenic potential, while subcellular localization analysis showed dominant outer membrane positioning for siderophore receptors and cytoplasmic localization for metabolic enzymes. The collective findings demonstrate that luteolin may exert antivirulence effects by interfering with iron uptake systems, destabilizing membrane-associated processes, and disrupting metabolic pathways essential for colonization and persistence, supporting its potential as a complementary therapeutic agent against enteric bacterial infections.